Current Trends in Computer Science and Mechanical Automation. Selected Papers from CSMA2016 - Volume 2 (2017)
The 2nd International Conference on Computer Science and Mechanical Automation carried on the success from last year and received overwhelming support from the research community as evidenced by the number of high quality submissions. The conference accepted articles through rigorous peer review process. We are grateful to the contributions of all the authors. For those who have papers appear in this collection, we thank you for your great effort that makes this conference a success and the volume of this proceeding worth reading. For those whose papers were not accepted, we assure you that your support is very much appreciated. The papers in this proceeding represent a broad spectrum of research topics and reveal some cutting-edge developments. Chapter 1 and 2 contain articles in the areas of computer science and information technology. The articles in Chapter 1 focus on algorithm and system development in big data, data mining, machine learning, cloud computing, security, robotics, Internet of Things, and computer science education. The articles in Chapter 2 cover image processing, speech recognition, sound event recognition, music classification, collaborative learning, e-government, as well as a variety of emerging new areas of applications. Some of these papers are especially eye-opening and worth reading. Chapter 3 and 4 contain papers in the areas of sensors, instrument and measurement. The articles in Chapter 3 cover mostly navigation systems, unmanned air vehicles, satellites, geographic information systems, and all kinds of sensors that are related to location, position, and other geographic information. The articles in Chapter 4 are about sensors and instruments that are used in areas like temperature and humidity monitoring, medical instruments, biometric sensors, and other sensors for security applications. Some of these papers are concerned about highly critical systems such as nuclear environmental monitoring and object tracking for satellite videos. Chapter 5 and 6 contain papers in the areas of mechatronics and electrical engineering. The articles in Chapter 5 cover mostly mechanical design for a variety of equipment, such as space release devices, box girder, shovel loading machines, suspension cables, grinding and polishing machines, gantry milling machines, clip type passive manipulator, hot runner systems, water hydraulic pump/motor, and turbofan engines. The articles in Chapter 6 focus on mechanical and automation devices in power systems as well as automobiles and motorcycles. This collection of research papers showcases the incredible accomplishments of the authors. In the meantime, they once again prove that the International Conference on Computer Science and Mechanical Automation is a highly valuable platform for the research community to share ideas and knowledge. Organization of an international conference is a huge endeavor that demands teamwork. We very much appreciate everyone who is involved in the organization, especially the reviewers. We are looking forward to another successful conference next year.